Evening choruses in the Perth Canyon and their potential link with Myctophidae fishes - McCauley, Robert; Cato, D. (Acoustical Society of America, 2016)
An evening chorus centered at near 2.2 kHz was detected across the years 2000 to 2014 from seabed receivers in 430-490 m depth overlooking the Perth Canyon, Western Australia. The chorus reached a maximum level typically 2.1 h post-sunset and normally ran for 2.1 h (between 3 dB down points). It was present at lower levels across most of the hours of darkness. Maximum chorus spectrum levels were 74-76 dB re 1 µPa2/Hz in the 2 kHz 1/3 octave band, averaging 6-12 dB and up to 30 dB greater than pre-sunset levels. The chorus displayed highest levels over April to August each year with up to 10 dB differences between seasons. The spatial extent of the chorus was not determined but exceeded the sampling range of 13-15 km offshore from the 300 m depth contour and 33 km along the 300 m depth contour. The chorus comprised short damped pulses. The most likely chorus source is considered to be fishes of the family Myctophidae foraging in the water column. The large chorus spatial extent and its apparent correlation with regions of high productivity suggest it may act as an acoustic beacon to marine fauna indicating regions of high biomass.